The role of tumor-stroma interactions on desmoplasia and tumorigenicity within a microengineered 3D platform. (July 2020) - Saini, Harpinder; Rahmani Eliato, Kiarash; Veldhuizen, Jaimeson; Zare, Azadeh; Allam, Mayar; Silva, Casey; Kratz, Alex; Truong, Danh; Mouneimne, Ghassan; LaBaer, Joshua; Ros, Robert; Nikkhah, Mehdi
Abstract: The tumor microenvironment has been demonstrated to play a crucial role in modulating cancer progression. Amongst various cell types within the tumor microenvironment, cancer associated fibroblasts (CAFs) are in abundance, serving to modulate the biophysical properties of the stromal matrix, through excessive deposition of extracellular matrix (ECM) proteins that leads to enhanced tumor progression. There is still a critical need to develop a fundamental framework on the role of tumor-stromal cell interactions on desmoplasia and tumorigenicity. Herein, we developed a 3D microengineered organotypic tumor-stroma model incorporated with breast cancer cells surrounded by CAF-embedded collagen matrix. We further integrated our platform with atomic force microscopy (AFM) to study the dynamic changes in stromal stiffness during active tumor invasion. Our findings primarily demonstrated enhanced tumor progression in the presence of CAFs. Furthermore, we highlighted the crucial role of crosstalk between tumor cells and CAFs on stromal desmoplasia, where we identified the role of tumor-secreted PDGF-AA/-BB on elevated matrix stiffness. Inhibition of the activity of PDGFRs in CAFs led to attenuation of stromal stiffness. Overall, our work presents a well-controlled tumor microenvironment model capable of dissecting specific biophysical and biochemical signaling cues which lead to stromal desmoplasia and tumor progression.